Relación entre espacio privado y espacio indiferenciado en viviendas del sitio Salinar de cerro Arena, valle de Moche. - Tantaleán Chiarot, Ana Gina (2018)
The present study approaches the spatial analysis of archaeological characterized places to have a great variability and heterogeneity in their architectural structures. An analytical approach was developed through the application of the spatial syntax that evaluated the social logic immersed in the relation between the private spaces and the undifferentiated or exterior space. 21 structures from the Salinar of Cerro Arena site in the Moche valley were described and analyzed using this methodology, ultimately achieving a typology of four variants of structures Salinar from their spatial circulation schemes. Finally, said spatial models are related to social processes linked to the household and strategies of power.